Adumbration of Amvrakia’s spring water pathways, based on detailed geophysical data (Kastraki - Meteora) - Alexopoulos, J.; Dilalos, S.; Vassilakis, Emm. (Advances in the Research of Aquatic Environment, 2011)
The Amvrakia spring is located at the bottom of Meteora pillars and more specifically near the village of Kastraki (Kalambaka municipality). It is a seasonal spring since it functions only during the wet period. The Meteora conglomerates which dominate the area are characterized by large discontinuities creating a network of groundwater pathways above the impermeable strata of the underlying marls. The research targets was to define these water pathways in order to understand the mechanism of Amvrakia spring, by mapping the exposed discontinuity network and define their underground extension with the contribution of geophysical techniques. Electrical Resistivity Tomography (ERT) and Very Low Frequency (VLF) methodologies were applied. The VLF method is indicated for the detection of water-bearing fracture zones, but before the application of their filters they had to be processed for topographic corrections, as the area had not smooth relief. Five (5) VLF profiles were conducted with different directions around the spring’s area, in order to detect possible conductive zones in the conglomerates surrounding the study area. Moreover, two (2) ERT sections of a total length of 140m were carried out, parallel to existent VLF sections, for crosschecking the geophysical information. Both techniques revealed important conductive zones (<200 Ohm.m) from the south-eastern Meteora conglomerate pillars, possibly interpreted as discontinuities filled with water feeding the spring.